Sport, human resources and basic values of japanese society - Maksimović Marijana (College of Sports and Health, Belgrade, 2020)
Japan is a capitalist country that puts profit at the center of the organization of industrial relations, but puts the "man" at the center of the organization of society and, accordingly, attaches great importance to human resources. Sport, as part of a healthy lifestyle, is one of the ways to promote longevity in Japan. In addition to many other elements, it contributes to a higher quality of life along with a particular diet. In Japan, stress is present because change is part of everyday life, and in the elimination of stress, it helps the sport as part of a healthy approach to life. Japan has a very long history of traditional martial sports and that are part of the budo, namely: judo, kendo, kyudo, sumo, karate-do, aikido, shorinji kempo, naginata, and jukendo. The very English term "martial arts" implies both martial sports and martial arts, though the two terms are distinguished. For example, a traditional martial sport is sumo, a martial arts is aikido, while karate is both a sport and a martial art. The main difference between martial sports and martial arts is that martial sports have competitions and firm rules in line with which athletes compete, while the arts have no contests and competition rules, but rather respect the principles of the martial art itself. Today, martial sports aim to improve a person's potential and abilities through learning, and to lead them to a fair triumph. The main point of martial arts is the acquisition of combat skills that are applicable in every situation.